A qualitative interview study of people living with well-controlled Type 1 diabetes. Issue 7 (3rd July 2018) - Smith, Debbie M.; Donnelly, Peter J.; Howe, John; Mumford, Terry; Campbell, Alan; Ruddock, Angela; Tierney, Stephanie; Wearden, Alison
Abstract : Objective: : While many people with Type 1 diabetes find it difficult to achieve recommended blood glucose levels, a minority do achieve good control. Our study was conceived by patient and public (PP) partners and sought to learn about experiences of people living with well-controlled diabetes. Design: : A collaboration between academic health psychologists and five PP partners with experience of diabetes, who were trained to conduct and analyse semi-structured interviews. Fifteen adults with well-controlled Type 1 diabetes were interviewed about the history of their diabetes and their current self-management practices. Interviews were subjected to inductive thematic analysis. Results: : Eight sub-themes were arranged into two overarching themes, 'facing up to diabetes' and 'balance leads to freedom'. Participants described a process of acceptance and mastery of diabetes, and talked about how they gained a deeper understanding of bodily processes through trial and error. Conclusion: : Based on the experiences of people with well-controlled Type 1 diabetes, interventions for people with this condition should encourage acceptance of the diagnosis and increasing confidence to experiment with behaviours (trial and error) to encourage 'mastery' of self-management. The research collaboration described here is an example of best practice for future researchers wanting to actively engage PP partners.